Matrix method usage in ecosystem services mapping: Adana Sarıçam sample - Gülay Tokgöz (Turkish Journal of Forestry, 2022)
The characteristics of ecosystems in terms of quality and quantity are changing and the pressure on natural resources is increasing in parallel with the rapid population growth. This change creates serious problems on land cover/land use and puts the risk on sustainable use of resources.. Therefore, potential analysis of ecosystem services has great importance in the land use management process. In this study, the effect of land cover/land use change on ecosystem services was investigated in Adana Sarıçam district. An expert-focused matrix method approach was used to assess the potential supply of ecosystem services from a holistic perspective. According to the ecosystem services result map created, it has been determined that the most important ecosystem services in the study area are arable lands, coniferous forests, meadow-pasture areas and maquis areas. It is aimed to use the land use data, ecosystem services matrices and maps obtained within the scope of the study as base data in planning studies.